Modulation of mRNA for microtubule-associated proteins during brain development. - Ginzburg, I (1982)
The heterogeneity of tau microtubule-associated proteins from rat brain is developmentally determined. Newborn rat brain contains two tau polypeptides (tau 0) with somewhat different molecular weights than the five tau components associated with microtubules from 12-day-old brain (tau 12). tau 0 and tau 12 are immunologically related and crossreact with antibodies against tau 12 proteins. Enrichment of the tau mRNA was achieved by prior hybridization of unfractionated poly(A)-containing mRNA to cDNA preparations containing tubulin and actin sequences. The remaining unhybridized mRNA was further fractionated by electrophoresis on methylmercury hydroxide agarose gels. Experiments involving cell-free translation of mRNA indicated that the major differences in the composition of tau proteins from newborn and developing brain are controlled at the mRNA level. The mRNA from newborn rat brain directed the synthesis of five tau proteins, two of which are specific for newborn brain, whereas the other three forms are characteristic of the developing brain. Thus, the appearance in newborn brain of mRNA species specific for three tau 12 forms precedes the phase of the synthesis of these proteins in the cell. By contrast, mRNA from 12-day brain directed the synthesis of four tau proteins specific for the developing brain, one of which is not synthesized by mRNA from newborn brain. None of the newborn tau 0 forms were synthesized with mRNA isolated from 12-day brain.